Proposed Organization of Agricultural Biomass Processing System in the Lublin Voivodship - Dobrowolski, Jacek; Łepecki, Andrzej; Łepecki, Łukasz (Regional Barometer. Analyses & Prognoses, 2011)
Agricultural biomass, defined as qualitatively different stream of organic matter derived directly or indirectly from agricultural crops, is functioning both in science and media. So far, scientific publications and journalists articles do not translate into actual operation of concrete plants in the region. Now is the time to discuss and prepare suitable model system for processing biomass. The authors describe in this article, their proposal for a comprehensive organization of the collection, processing and supply of agricultural biomass taking into account: needs of energy industry, agrarian structure of Lubelskie Voivodship and crop diversity. The main component of the possible flow of agricultural biomass to be processed for the power sector is the straw of cereals but hay which is quite underestimated is an abundant in the region. Because of the wide variation in types of raw material and fragmentation of agricultural holdings a special system for collecting, processing and transporting biofuels should be prepare. The basic organizational unit should be relatively small processing plant cooperating with all the farmers eager to sell their biomass. This unit should also work as a buffer magazine for biomass and compressed (ready to transport) biofuels. To ensure the coherence of the system, activities of all the processing plants are subjected to the control of one body. Implementing the described solutions guarantees: employment for several hundred people, unification of produced biofuels according to quality and physical features, uniformity of supply chain, eliminating health and safety problems associated with the organization of work of agricultural equipment and ease to extend the system in case of increased demand.